CURRENT ASPECTS OF PRACTICAL APPLICATION OF COMPUTER TECHNOLOGY IN THE EDUCATIONAL PROCESS OF TECHNICAL UNIVERSITIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The article reveals the theoretical foundations of modern engineering and pedagogical education, proposes the author's vision of the essence of the professional competence of a transport system engineer, the main approaches to his preparation and the results of their use in the educational process of technical universities.